Stories and Plays: Ethnography, Performance and Ethical Engagements - Culhane, Dara (Anthropologica, 2022)
This article offers an account of an intentionally Utopian ethnographic project, carried out in Vancouver’s Down- town Eastside. The "Stories and Plays Project" explored con- ditions of possibility for experiencing ethical engagements between researchers and research subjects in a context of deeply commodified research relationships dominated by biomedical and pharmaceutical research, and advanced marginalization. Articulating ethnography and performance methodologies within a framework shaped by improvisation as concept and practice, and committed to ethical-political relations of field- work processes over representational products, the project included an alternative, three-stage consent process. This arti- cle draws on current debates about theorizing fieldwork, engages in interdisciplinary debate, and seeks to provoke reflec- tions on a "new," emerging experimental ethnography.